An Examination of Individual Differences and Factor Structure on the LS/CMI: Does This Popular Risk Assessment Tool Measure Up?. Issue 3 (4th March 2017) - Schmidt, Nicole; Lien, Emily; Vaughan, MaryFaith; Huss, Matthew T.
ABSTRACT: The Level of Service/Case Management Index (LS/CMI) is the most commonly used case management tool among frontline criminal justice officials. However, the newest revision has been understudied. Literature suggests significant differences on Level of Service Inventory (LSI) and LSI–Revised subcomponents and total scores among various offender populations. Such differences, along with an overall lack of psychometric information, have significant implications for the use of this instrument. The current study examined the records of 200 consecutively supervised probationers for demographic information, criminal history, most recent crimes, mental health issues, substance use and abuse, and their LS/CMI scores for both offender group differences and factor structure.